Correlation Between Emotional Peer Support and Cyberbullying Behaviour in Senior High School Students - Emi Wuri Wuryanningsih; Enggal Hadi Kurniyawan; Emila Cahya Aisyah (Universitas Airlangga, 2019)
ABSTRACTIntroduction: The biggest users of the internet and social media are teenagers. This has an impact on the tendency for harassment behavior known as cyber-bullying. This harassment is quite serious because it is massive; it can happen at any time and anywhere. This harassment generally comes from the victim’s peers. This research aimed to analyze the correlation between peer emotional support and the cyber-bullying behavior among the students in senior high school.Methods: This research used a cross-sectional study design. The sample size of this study was 246 students in senior high school from the academic year 2018-2019 collected through purposive sampling. The instrument of this research was emotional support from their peers and cyberbullying behavior. The bivariate analysis used was the Spearman test (α<0.05; CI=95%).Results: There is a significant correlation between emotional peer support and cyberbullying behavior among the students in senior high school.Conclusion: Community health nurses should improve the emotional peer support among the students in order to promote the prevention of cyberbullying behavior.